ANALISIS RASIO KEUANGAN PADA PT INDOFOOD SUKSES MAKMUR TBK PERIODE 2018-2022 - Rizki Firdaus, Muhammad; Wartono, Tri (Journal of Research and Publication Innovation, 2024)
This study aims to analyze and evaluate the liquidity performance, profitability level, solvency level, and operational efficiency of PT Indofood Sukses Makmur Tbk (INDF) during the period of 2018-2022. The research method used is descriptive analysis, which involves calculating and illustrating financial ratios, horizontal analysis by comparing INDF's financial statements year-on-year, and comparative analysis by comparing INDF's financial statements with those of five similar companies in the food and beverage industry. The analyzed ratios include Current Ratio (CR), Cash Ratio (CAR), Return on Assets (ROA), Return on Equity (ROE), Debt to Asset Ratio (DAR), Debt to Equity Ratio (DER), Total Asset Turnover (TATO), and Inventory Turnover (ITO). Data is derived from INDF's annual financial statements and industry averages. The results show that INDF's liquidity is lower than the industry average. INDF’s CR ranges from 106.63%-178.60% while the industry average is 355.53%-399.59%. INDF’s CAR increased from 28.23% in 2018 to 84.44% in 2022, but remains below the industry average. INDF’s ROA varies between 5.09%-6.25% compared to the industry average of 6.45%-18.43%. INDF’s ROE reached 12.93% in 2021, while the industry average ranges from 0.45%-33.05%. INDF’s DAR is 43.66%-51.70% and DER is 77.48%-107.03%, both higher than the industry average. INDF’s operational efficiency, measured by TATO and ITO, is also lower. It is recommended that INDF improve liquidity, profitability, solvability, and operational efficiency through cash management strategies, cost control, product diversification, debt restructuring, and technology investment.